Empowering Education: Harnessing AI for Society 5.0 - Kristianti, Tri (International Journal of Theory and Application in Elementary and Secondary School Education, 2024)
Era Society 5.0 emphasized the concept of humanized technology due to the necessity of a society that genuinely integrates the physical and virtual worlds. The implication of modern technology in the era of Society 5.0 covers Artificial Intelligence (AI), robots, and the Internet of Things (IoT). The involvement of modern technology has been applied in three primary sectors; economics, industry, and education to support the needs of society. Applying modern technology based on Artificial Intelligence (AI) for educational purposes is interesting yet challenging. This research aims to study and compare the two tools of Artificial Intelligence based on their functions, features, and safety, namely Google Bard (now Gemini) and ChatGPT. Therefore, the method used in this research is a comparative study using practical and literature studies as the primary data. This research can provide beneficial results in technology literacy for educational practitioners to conduct future research viewing from different perspectives.